Blood Pressure and Heart Rate Screenings in Physical Therapy: An Interprofessional DNP Project - Bullock, Elyse (My University, 2018)
Physical therapists are increasing their autonomous practice, which includes direct patient referral without a provider first assessing the patient. The Guide to Physical Therapist Practice recommends that every patient being seen for physical therapy should have a cardiopulmonary system review. Review of literature shows that physical therapists are not routinely performing blood pressure (BP) and heart rate screenings on their patients. The purpose of this DNP project was (1) to educate physical therapists the importance of measuring BP and heart rate values for patients being seen for physical therapy (2) to establish a policy and procedure for BP and heart rate assessments prior to physical therapy sessions, (3) and to teach physical therapists steps for healthcare provider referrals and steps for interprofessional communication for abnormal BP and heart rates. Methods included (1) BP and heart rate screening and related analysis education for providers, (2) policy and procedure development and education for the clinic (3) healthcare provider referrals and interprofessional communication education, (4) and development of a BP and heart rate audit tool for providers. Results showed that the methods implemented did not change frequency of blood pressure and heart rate screenings. Results did show physical therapists stopping sessions and performing provider referrals based on BP and heart rate values. Implications of this project were safe practice and the importance of BP and heart rate screenings before physical therapy because BP and heart rate readings could be contraindications for physical therapy.
Keywords: Evidence-based practice; blood pressure; heart rate; physical therapy